Burnout in pediatric hematology oncology fellows: Results of a cross‐sectional survey. Issue 11 (11th April 2020) - Moerdler, Scott; Li, Yunhui; Weng, Shicheng; Kesselheim, Jennifer
Abstract: Burnout is a significant problem in the medical community, including among pediatric hematology/oncology (PHO) faculty. However, the prevalence of burnout, its associated risk factors, and outcomes within PHO fellows are unknown. We present the results of a cross‐sectional study of PHO fellows from 21 training programs. A total of 45/115 fellows (39.1%) met criteria for high level of burnout. Fellows who met criteria for high burnout also demonstrated poor outcomes including decreased empowerment, increased doctor‐centered care, decreased self‐assessed humanism, and decreased satisfaction with training. Further longitudinal investigation is needed to better understand burnout and the causative factors affecting PHO fellows.